Соматичні мутації сортів інтродукованих садових троянд у колекції Національного ботанічного саду імені М.М. Гришка - Rubtsova, Olena; Chyzhankova, Valentina (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2026)
The article analyzes the manifestations of somatic (bud) mutational variability of traits in garden roses (Rosa L.) under the conditions of the collection of the M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine. The study is based on the results of long-term phenotypic observations of cultivars of different origin and garden groups. It was established that mutational variability in roses is not random but follows regular and largely predictable patterns determined by the genotype, origin, and breeding history of the initial cultivars. A relationship between the direction of mutational changes and the affinity of cultivars with particular garden groups was revealed: forms closer in origin to wild rose species more frequently produce mutants with enhanced expression of decorative traits, whereas cultivars of modern, evolutionarily advanced groups predominantly give rise to mutants with reduced expression of these traits. Both stable somatic mutants and cases of partial or complete reversion to the phenotype of the original cultivar were recorded. The practical significance of somatic mutations for cultivar assessment, cultivar identification, trait stability assessment, and mutation breeding in ornamental plants is substantiated.